The Effect of The LENTERA Educational Video (Stand Against Early Marriage to Illuminate Adolescents’ Future) on The Knowledge Levels of Female Adolescents Regarding The Dangers of Early Marriage - Nabila Naili Firdaus; Wiwin Mintarsih Purnamasari; Uly Artha Silalahi (Jurnal Kebidanan, 2025)
Early marriage remains a prevalent issue with significant impacts on the physical, psychological, and social well-being of adolescent girls. A lack of knowledge about the dangers of early marriage is one of the primary contributing factors to its occurrence. This study aims to analyze the effect of the LENTERA educational video (Stand Against Early Marriage to Illuminate Adolescents’ Future) on female adolescents’ knowledge levels regarding the dangers of early marriage. A pre-experimental method with a one-group pretest-posttest design was employed in this research, conducted at SMPN 16 Tasikmalaya in 2025. The sample consisted of 46 female adolescents selected using a simple random sampling technique. Data were collected using questionnaires and analyzed using the Paired Sample T-Test. The results showed that the mean knowledge score before the intervention was 67.83 (moderate category) and increased to 86.46 (good category) after the intervention, with a p-value < 0.05. In conclusion, the LENTERA educational video effectively improved the knowledge levels of female adolescents regarding the dangers of early marriage. This video is recommended as an educational tool for reproductive health to reduce early marriage rates among adolescents.